PEDAGOGICAL CULTURE OF THE FUTURE TEACHER, ITS ROLE IN TEACHING AND EDUCATION OF THE CHILD'S PERSONALITY IN THE INTEGRATED ENVIRONMENT (Pedagogy of Higher and Secondary Education, 2009)
The article is devoted to the research of the importance of pedagogical culture of a future teacher. The pedagogical condition of future teacher's pedagogical culture (integrity , continuity, rystematic character) formation have been dearmined in the article.
Keywords: teacher; pedagogical culture; pedagogical conditions